Persistency of Mesenchymal Stromal/Stem Cells in Lungs - Ferrini, Erica; Stellari, Fabio Franco; Franceschi, Valentina; Macchi, Francesca; Russo, Luca; Murgia, Alba; Grisendi, Giulia; Villetti, Gino; Dominici, Massimo; Donofrio, Gaetano (Frontiers in Cell and Developmental Biology, 2021)
Mesenchymal stromal/stem Cells (MSCs) are a fibroblast-like cell population with high regenerative potential that can be isolated from many different tissues. Several data suggest MSCs as a therapeutic tool capable of migrating to a site of injury and guide tissue regeneration mainly through their secretome. Pulmonary first-pass effect occurs during intravenous administration of MSCs, where 50 to 80% of the cells tend to localize in the lungs. This phenomenon has been exploited to study MSCs potential therapeutic effects in several pre-clinical models of lung diseases. Data demonstrated that, regardless the lung disease severity and the delivery route, MSCs were not able to survive longer than 24h in the respiratory tract, but still surprisingly determining a therapeutic effect. In this work, two different mouse bone marrow derived MSCs (mBM-MSCs) lines, stably transduced with a third-generation lentiviral vector expressing Luciferase and GFP reporter genes tracking MSCs in vivo biodistribution and persistency, have been generated. Cells within the engrafted lung were in vivo traced using the high throughput Bioluminescence Imaging (BLI) technique, with no invasiveness on animal, minimizing biological variations and costs. In vivo BLI analysis allowed the detection and monitoring of the mBM-MSC clones up to 28 days after implantation, independently from the delivery route. This longer persistency, than previously observed (24 hours), could have a strong impact in terms of pharmacokinetic (PK) and pharmacodynamics (PD) of MSCs as a therapeutic tool.